VIDEO BRANDING UNTUK PROMOSI TAMAN KUMBASARI SEBAGAI UPAYA PENINGKATAN MINAT WISATAWAN BERWISATA - Semara, I Made Trisna; I Putu David Adi Saputra; Ayu Suwita Yanti (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2023)
Product branding or marketing has now evolved from static images to videos. The right video can give an in-depth image to tourists to come on a trip to the tourist attraction. Making appealing branding videos needs skills in taking photos and creating a captivating plot, packaging the videos by editing sound and pictures, adding text and dubbing. After COVID-19, Kumbasari Park has not been able to increase foreign and domestic tourist visits. This is because tourist attractions have not been able to optimize their branding. As a solution to this problem, community service activities are carried out. The dedication is aimed at boosting tourism by increasing visits to tourist attractions. This is because the Denpasar City tourism office has not optimized promotional media through videography. This community service activity is to create promotional videography and utilize social media to make tourist attractions viral through Instagram/TikTok accounts owned by IPB International students. In addition, the implementation team will also help disseminate videos by reposting videos to other accounts owned by IPB International students. The goal is to introduce and make tourist attractions viral to attract tourists to come and revisit for tourism.